(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
A geometric analysis is conducted on eight proposed sites for the construction of rainwater harvesting dam reservoirs to build rainwater harvesting dams in Wadi Al-Qasab, This give the importance of these dams in providing water to the residents of the villages surrounding Wadi Al-Qasab and in increasing the agricultural areas of ​​these lands, which have been affected by climate fluctuations and scarcity of rain in recent years, in addition to protecting these areas from the dangers of torrents and floods, A digital elevation model with a resolution of (10mx10m) is used in the study to deduct the boundaries of the reservoirs in each of the selected sites, and geological programs are applied such as (Global Mapper, ArcGIS, Surfer) to deduce and extract the geometric elements that include the positive volume PV (volume of islands within the reservoir), negative volume NV (volume of water storage), positive surface area (PSA, the area of ​​islands within the reservoir), negative surface area NSA (area of ​​the reservoir bottom or wetted area), positive planar area (PPA, the area of island projections within the reservoir boundaries), and average depth of the reservoir (AD). Relationships are found between the geometric elements and the proposed dam sites to determine the best sites as a water reservoir, and it is shown through these relationships that the second site in the village of Nazaza represents the best sites as a water reservoir.